Sekolah Peduli Pandemik Melalui Pelatihan Pembuatan Media Pembelajaran Masker Kipas Micro Brushless untuk Memaksimalkan Tekanan dan Kecepatan Udara Pernapasan - Ketut Alit Adi Untara; Ketut Alit Adi Untara; Kamaluddin Kamaluddin; Muslimin Muslimin; Syamsu Syamsu (Universitas Tadulako, 2022)
In the pandemic Covid-19 era, schools are required to obey the health protocol. The Covid-19 handling health team requires a health protocol that is always wearing a mask, washing hands with soap or hand sanitizer, maintaining distance, and cleaning the room with disinfectant. However, the awareness of using masks by teachers and students in schools is still low. The general complaint that is felt is difficult to breathe by using a mask for a long time. The difficulty of breathing by using a mask because the inhaled air will experience obstacles that enter the nose. The problem of obstructing air breathing air with a mask needs to be repaired by the mask to be comfortable to use. The concept of air movement concerns its pressure and speed on learning taught in pressure and speed material. This concept becomes the basis in understanding the circulation of respiratory air that occurs in the mask. By looking at this interesting situation it is necessary to make a physics learning media that can be used directly by students or teachers and in accordance with the current pandemic conditions. Making alearning media is summarized in training activities for making micro brushless fan masks. The training provided is a way to make a micro brushles fan mask that can control the Covid-19 virus, students and teachers can produce products that are useful and can be used directly at school which ultimately has a big impact on the community.